Rare non-Hodgkin lymphoma of childhood and adolescence: A consensus diagnostic and therapeutic approach to pediatric-type follicular lymphoma, marginal zone lymphoma, and nonanaplastic peripheral T-cell lymphoma - Attarbaschi, Andishe; Abla, Oussama; Arias Padilla, Laura; Beishuizen, Auke; Burke, G A Amos; Brugières, Laurence; Bruneau, Julie; Burkhardt, Birgit; d'Amore, Emanuele S G; Klapper, Wolfram; Kontny, Udo; Pillon, Marta; et al. (Pediatric blood & cancer, 2020)
Pediatric-type follicular (PTFL), marginal zone (MZL), and peripheral T-cell lymphoma (PTCL) account each for <2% of childhood non-Hodgkin lymphoma. We present clinical and histopathological features of PTFL, MZL, and few subtypes of PTCL and provide treatment recommendations. For localized PTFL and MZL, watchful waiting after complete resection is the therapy of choice. For PTCL, therapy is subtype-dependent and ranges from a block-like anaplastic large cell lymphoma (ALCL)-derived and, alternatively, leukemia-derived therapy in PTCL not otherwise specified and subcutaneous panniculitis-like T-cell lymphoma to a block-like mature B-NHL-derived or, preferentially, ALCL-derived treatment followed by hematopoietic stem cell transplantation in first remission in hepatosplenic and angioimmunoblastic T-cell lymphoma.
Keywords: Female; Infant; dítě; předškolní dítě; alografty; Lymphoma, B-Cell, Marginal Zone; periferní T-buněčný lymfom; ženské pohlaví; Adolescent; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; Lymphoma, Follicular; Male; kojenec; Allografts; mladiství; Child, Preschool; Lymphoma, T-Cell, Peripheral; folikulární lymfom; Child; mužské pohlaví; lymfom z B-buněk marginální zóny; Humans